AKUNTANSI NGO DAN AKUNTABILITAS: IMPLEMENTASI GLOBAL FUND, BUDAYA MENOLONG, DAN PENGETAHUAN AKADEMISI - Izzah, Nisfatul (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. This study aims to produce research on the development of new products of NGO accountability. This study describes the implementation and accounting treatment of foreign grants The Global Fund AIDS Tuberculosis and Malaria (GFATM) in Sub Recipient TB Care ‘Aisyiyah Jatim (SR).Research Methods. This study uses qualitative methods with data triangulation instruments.Research Result and Findings. The results showed that GFATM grant accounting process and accountability is very systematic, structured, complete and strict. Accountability can be realized from a helping behavior and providing NGO accounting education from the academic level. The implementation of foreign grant accounting and NGO accountability in this study is very important both empirically and theoretically as a reference for NGO managers, foreign grant activists and new knowledge from academics. Beneficiaries can prepare accounting and accountability of non-profit organizations properly and correctly.